The features of foot morphology and intrinsic foot muscle property in adolescent swimmers: an ultrasound-based study - Kaneda, K.; Maeda, N.; Ikuta, Y.; Tashiro, T.; Tsutsumi, S.; Arima, S.; Sasadai, J.; Suzuki, Y.; Morikawa, M.; Komiya, M.; Adachi, N.; Urabe, Y. (Journal of Human Kinetics, 2023)
This cross-sectional study aimed to investigate the relationship between foot shape and intrinsic foot muscles (IFMs) in adolescent swimmers compared with other athletes. Foot morphology of swimmers was compared with other athletes of comparable age and a competition level (n = 32 [64 feet]; a total of 64 feet; 128 feet in two groups). Foot morphology and variables of IFMs were measured using a three-dimensional foot scanner and an ultrasound imaging system, respectively. Multiple linear regression analysis with forced entry was performed to clarify the association of the thickness and the cross-sectional area (CSA) of IMFs with the navicular height in both sitting and standing positions. Navicular height in a standing position, the thickness of the abductor hallucis (AbH) and the flexor digitorum brevis (FDB), as well as the CSA were significantly lower in swimmers compared with other athletes (p < 0.05). A larger CSA for the flexor hallucis brevis (FHB) was observed in swimmers than in other athletes (p < 0.01). The navicular height of swimmers in sitting and standing positions was positively correlated with the thickness and the CSA of the FHB and the FDB (p < 0.05). Multiple regression analysis showed that navicular height was associated with the CSA of the FDB in both sitting and standing positions (ß = 0.395; p < 0.002, ß = 0.201; p < 0.018). This study showed that the navicular height of elite adolescent swimmers was lower than that of other athletes. Furthermore, the swimmers` high navicular height was associated with the CSA of the FDB, suggesting that the FDB might be more involved in the formation of the medial longitudinal arch than the AbH.